KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA PENGARUH BRAND AWARENESS, HARGA DAN DISTRIBUSI TERHADAP KEPUASAN PELANGGAN PRODUK TRANSDERMAL PATCH - Peri Retno Nurhayati; Rena Febrita Sari (Jurnal Ekonomi, Bisnis dan Social, 2024)
The study's overarching objective is to learn what aspects of transdermal patch products most positively affect customers' satisfaction. This study employs a descriptive research strategy based on a survey. Samples for this research were chosen systematically for a specific purpose. 75 clients of PT Indo Abadi Sarimakmur (INDOSAR) participated in the survey. Only brand recognition, price, and distribution's impacts on consumers' happiness are investigated here. Using inner and outer models and hypothesis testing (bootstrapping), a structural equation modelling technique (SmartPLS 4.0.9.3) is used to probe the significance of the whole model and its specified paths. According to the findings, customer brand identification is a major factor in the purchase of chilli patches in Surabaya. The price of chilli plants is a crucial consideration for consumers in Surabaya. The distribution of chilli patches has a significant effect on their availability for purchase in Surabaya. In Surabaya, one's satisfaction with a certain brand of chilli paste is connected to one's familiarity with that brand. Consumers in Surabaya are not particularly bothered about the cost of chilli paste. In Surabaya, the distribution of chilli paste has a major effect on customer happiness. The availability of fresh chilli patches for sale has a substantial effect on Surabaya's customer happiness.